Hypoxic Conditions in Crown Galls Induce Plant Anaerobic Responses That Support Tumor Proliferation - Kerpen, Lucy; Niccolini, Luca; Licausi, Francesco; van Dongen, Joost T.; Weits, Daan A. (Frontiers in Plant Science, 2019)
Agrobacterium tumefaciens infection of wounded plant tissues causes the formation of crown gall tumors (Escobar and Dandekar, 2003). Upon infection, genes encoded on the A. tumefaciens tumor inducing plasmid are integrated in the plant genome to induce the biosynthesis of auxin and cytokinin, leading to uncontrolled cell division. Additional sequences present on the bacterial T-DNA encode for opine biosynthesis genes, which induce the production of opines that act as a unique carbon and nitrogen source for Agrobacterium (Escobar and Dandekar, 2003; Guyon et al., 1980). Crown galls therefore become a very strong sink for photosynthate. Here we found that the increased metabolic demand in crown galls causes an increase in oxygen consumption rate, which leads to a steep drop in the internal oxygen concentration. Consistent with this, plant hypoxia-responsive genes were found to be significantly upregulated in crown galls compared to uninfected stem tissue. Following this observation, we aimed at understanding whether the low-oxygen response pathway, mediated by group VII ETHYLENE RESPONSE FACTOR (ERF-VII) transcription factors, plays a role in the development of crown galls. We found that quintuple knock-out mutants of all ERF-VII members, which are incapable of inducing the hypoxic response, show reduced crown gall symptoms. Conversely, mutant genotypes characterized by constitutively high levels of hypoxia-associated transcripts, displayed more severe crown gall symptoms. Based on these results, we concluded that uncontrolled cell proliferation of crown galls established hypoxic conditions, thereby requiring adequate anaerobic responses of the plant tissue to support tumor growth.